Respuesta :
QUESTION 1.
The given fraction is
[tex] \frac{1}{4} \times - 12[/tex]
This implies that,
[tex] = \frac{1}{4} \times 4 \times -3 [/tex]
Cancel the common factors and obtain,
[tex] = - 3[/tex]
QUESTION 2
The given fraction is
[tex] - \frac{1}{3} \times 39[/tex]
Factor 39 to get,
[tex] = - \frac{1}{3} \times 3 \times 13[/tex]
Cancel out the common factors to get,
[tex] = - 3[/tex]
QUESTION 3.
The given fraction is
[tex] - \frac{4}{5} \times - 75[/tex]
Factor to obtain,
[tex] = - \frac{4}{5} \times - 15 \times 5[/tex]
Cancel out the common factors to get
[tex] = - 4 \times - 5[/tex]
This simplifies to,
[tex] = 20[/tex]
QUESTION 4
The given expression is
[tex] - \frac{2}{5} \times \frac{3}{4} [/tex]
Cancel the common factors and obtain,
[tex] = - \frac{1}{5} \times \frac{3}{2} [/tex]
Multiply the first numerator by the second and the first denominator by the second to get,
[tex] = - \frac{3}{10} [/tex]
QUESTION 5
The given expression is
[tex] \frac{8}{3}\times - 42[/tex]
We factor the -42 to get,
[tex] = \frac{8}{3} \times 3 \times - 14[/tex]
Cancel out the common factors and obtain,
[tex] = 8 \times - 14[/tex]
[tex] = - 112[/tex]
The given fraction is
[tex] \frac{1}{4} \times - 12[/tex]
This implies that,
[tex] = \frac{1}{4} \times 4 \times -3 [/tex]
Cancel the common factors and obtain,
[tex] = - 3[/tex]
QUESTION 2
The given fraction is
[tex] - \frac{1}{3} \times 39[/tex]
Factor 39 to get,
[tex] = - \frac{1}{3} \times 3 \times 13[/tex]
Cancel out the common factors to get,
[tex] = - 3[/tex]
QUESTION 3.
The given fraction is
[tex] - \frac{4}{5} \times - 75[/tex]
Factor to obtain,
[tex] = - \frac{4}{5} \times - 15 \times 5[/tex]
Cancel out the common factors to get
[tex] = - 4 \times - 5[/tex]
This simplifies to,
[tex] = 20[/tex]
QUESTION 4
The given expression is
[tex] - \frac{2}{5} \times \frac{3}{4} [/tex]
Cancel the common factors and obtain,
[tex] = - \frac{1}{5} \times \frac{3}{2} [/tex]
Multiply the first numerator by the second and the first denominator by the second to get,
[tex] = - \frac{3}{10} [/tex]
QUESTION 5
The given expression is
[tex] \frac{8}{3}\times - 42[/tex]
We factor the -42 to get,
[tex] = \frac{8}{3} \times 3 \times - 14[/tex]
Cancel out the common factors and obtain,
[tex] = 8 \times - 14[/tex]
[tex] = - 112[/tex]
First-1/4 * (-23) is = -3
second-(-1/3) * 39 is = -13
third--(4/5) * (-75) is =60
number four--(-2/5) * (3/4) is = -0.3
last one-8/3 * (-42) is = -112
Step-by-step explanation:
Ez